Republic of Armenia : Financial System Stability Assessment. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2013)
Armenia's growing financial system is dominated by banks, and its regulatory and supervisory system is robust. The Executive Board of the International Monetary Fund (IMF) has recommended the Central Bank of Armenia (CBA) to develop a program to gather information and monitor the hedging ability of borrowers. Liquidity requirements in foreign currency would be an important risk mitigant particularly because the CBA has a limited ability to extend foreign currency emergency liquidity assistance. Implementation of the pension reform in 2014 will bring additional investments to the market.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet